(untitled) (Revista de Investigaciones Universidad del Quindío, 2016)
This paper proposes a fuzzy inference system for color manipulation in digital images to change the art style to psychedelic art. Initially through sets and fuzzy inference rules, generating images with colors characteristic of this type of art. Later fi ts inference system with the technique proposed an optimization algorithm based on particle swarms evidencing improved results.